Virtual monitoring for stable chronic hepatitis B patients does not reduce adherence to medications: A randomised controlled study. (May 2023) - Kumar, Rajneesh; Yee, Mei-Ling; Goh, George BB; Chia, Pei-Yuh; Lee, Hwei-Ling; Xin, X; Teo, Pek SE; Ekstrom, Victoria SM; Tan, Jin YT; Cheah, Mark CC; Wang, Yu T; Chang, Jason PE; et al.
Introduction: Chronic hepatitis B (CHB) remains common in endemic regions, causing significant healthcare burden. Patients with CHB may need to be adherent to nucleoside analogue (NA) for a long period of time to prevent complications. This study aims to investigate the safety, efficacy and patient experience of a virtual monitoring clinic (VMC) in monitoring stable patients taking NA for CHB. Methods: Patients on NA and regular follow-up were randomised to either VMC alternating with doctors' clinic visit or to a control group in which they continued standard follow-up by doctors. Therapy adherence was measured by medication possession ratio (MPR) for NA therapy, incidence of virological breakthrough and hepatocellular carcinoma (HCC) development at two years of follow-up. Patient acceptance was measured on a Likert scale of 1–10. Results: A total 192 patients completed follow-up: 94 and 98 patients in the VMC and control groups, respectively. Mean age was 60.6 ± 10.8 years, with 95.3% Chinese ethnicity and 64.1% males. Age, gender, race, educational, employment and financial status were similar in both groups. Upon study completion, the majority of patients – 76 (80.9%) in VMC group and 74 (75.5%) in control group – had MPR ≥0.8; 88.8% were satisfied and rated VMC better than a traditional follow-up clinic with doctors only. More than 85% of patients rated ≥8/10 on the Likert scale for VMC, and preferred VMC over traditional clinic visits. Clinical outcomes observed were HCC development in one (1.1%) in the VMC group and four (4.1%) in the control group ( p = 0.369). Two (2.1%) and one (1.0%) virological breakthroughs were observed in the VMC and control groups, respectively ( p = 0.615). No incidence of HCC or abnormal blood tests were missed in the VMC arm. Discussion: VMC is a viable and safe clinical model for monitoring stable CHB patients on NA therapy without compromising patients' adherence to medications and is preferred by patients.